2012
DOI: 10.1364/oe.20.007749
|View full text |Cite
|
Sign up to set email alerts
|

Temporal broadening of optical pulses propagating through non-Kolmogorov turbulence

Abstract: General formulations of the temporal averaged pulse intensity for optical pulses propagating through either non-Kolmogorov or Kolmogorov turbulence are deduced under the strong fluctuation conditions and the narrow-band assumption. Based on these formulations, an analytical formula for the turbulence-induced temporal half-width of spherical-wave Gaussian (SWG) pulses is derived, and the single-point, two-frequency mutual coherence function (MCF) of collimated Gaussian-beam waves in atmospheric turbulence is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In other words, the transmittance introduced by pulse broadening is actually negligible in the regime of weak turbulence. However, in the regime of strong turbulence, the analysis of equation (18) requires a large amount of numerical calculations [34]. In [34], the results also show that broadening is only perceptible on the order of femtosecond in strong turbulence, i.e., the broadening-induced transmittance approaches one, thus negligible.…”
Section: Transmittance: Temporal Pulse Broadeningmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, the transmittance introduced by pulse broadening is actually negligible in the regime of weak turbulence. However, in the regime of strong turbulence, the analysis of equation (18) requires a large amount of numerical calculations [34]. In [34], the results also show that broadening is only perceptible on the order of femtosecond in strong turbulence, i.e., the broadening-induced transmittance approaches one, thus negligible.…”
Section: Transmittance: Temporal Pulse Broadeningmentioning
confidence: 95%
“…However, in the regime of strong turbulence, the analysis of equation (18) requires a large amount of numerical calculations [34]. In [34], the results also show that broadening is only perceptible on the order of femtosecond in strong turbulence, i.e., the broadening-induced transmittance approaches one, thus negligible. Therefore, there is no need to consider the transmittance change caused by pulse broadening in the following performance analysis in section 4.…”
Section: Transmittance: Temporal Pulse Broadeningmentioning
confidence: 95%
“…We will discuss some of these results below on considering the applications. The evolution of the second-order statistics of non-stationary (pulsed) fields in non-Kolmogorov turbulence was treated in [98,99].…”
Section: Theoretical Predictions For Non-classic Turbulence-light Interactionsmentioning
confidence: 99%
“…For the 3D image, studying on the ELPP affected by atmospheric turbulence is significant to improve resolution and accuracy in practical applications [11]. To the best of our knowledge, previous studies have shown that the ELPP is mainly affected by the response of detectors [12], targets shape [13] and atmosphere, etc [14]. Although previous studies have presented relative results on the ELPP affected by targets [5,15,16], the results are based on the assumption of neglecting effect from atmospheric turbulence.…”
Section: Introductionmentioning
confidence: 99%